Equações algébricas : história e ensino - Vertuoso, Valcir Borges (2019)
In this paper, we present the solution process of solving algebraic equations took place from ancient civilizations to the beginning of modernity. We will expose, in short, how the search for solving formulas of algebraic equations using radicals (operations involving sum, subtraction, multiplication, division, root and potentiation), culminating with the ideas of the young mathematician Evariste Galois, who ended the search for a general formula ` for equations of 5 or more. Along this route, we have sought to highlight the importance of the history of mathematics as a resource for teaching mathematics, in particular for teaching algebraic equations.